2020
DOI: 10.1371/journal.pone.0239000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of participant-collected nasal and staff-collected oropharyngeal specimens for human ribonuclease P detection with RT-PCR during a community-based study

Abstract: We analyzed 4,352 participant-and staff-collected respiratory specimens from 2,796 subjects in the Oregon Child Absenteeism due to Respiratory Disease Study. Trained staff collected oropharyngeal specimens from school-aged children with acute respiratory illness while household participants of all ages collected their own midturbinate nasal specimens in year one and anterior nasal specimens in year two. Human ribonuclease P levels were measured using RT-PCR for all staff-and participant-collected specimens to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This was mirrored in the observed C T values for the detection of respiratory microbes. RT-PCR-based assays have limitations and are highly sensitive, highlighting C T value variability when measuring human cell loads harvested by swabbing different upper respiratory tract sample sites or comparing collection methods (24). We found that PC nasal swab samples contained more biological material and respiratory microbes, compared to NC swab samples.…”
Section: Discussionmentioning
confidence: 81%
“…This was mirrored in the observed C T values for the detection of respiratory microbes. RT-PCR-based assays have limitations and are highly sensitive, highlighting C T value variability when measuring human cell loads harvested by swabbing different upper respiratory tract sample sites or comparing collection methods (24). We found that PC nasal swab samples contained more biological material and respiratory microbes, compared to NC swab samples.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to the detection of SARS-CoV-2, two other targets linked to human contamination were quantified in this work. One of them was the gene that encodes for human RNase P, which was used in many studies as an endogenous internal control (Arnold et al, 2020;Boddicker et al, 2007;Dahdouh, et al, 2020), and it has been extensively used as a sample quality control in clinical tests in the current COVID-19…”
Section: Discussionmentioning
confidence: 99%
“…From 5 January 2015 through 13 March 2020, study team members made home visits to collect demographic, epidemiologic, and symptom data (supplemental form); nasal swab (NS) specimens; and high oropharyngeal (OP) specimens. The study protocol changed on 14 March 2020 to no-contact drop off and pick up of data forms and supplies for the self-collection [ 14 ] of NS specimens and has continued in this manner.…”
Section: Methodsmentioning
confidence: 99%